Social Emotional Ability Children with Special Needs in Novel Sakura's Secret: A Piece of The Secret about Which Can Never be Perfect - Mustakimah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
By nature, every human being is born in a state of goodness from all sides. Good or bad their physical condition is not a barrier for them to become good people with all their potential. Having a defect in their body is not something they ask for and even if they can't deny it because it has become a written lifeline. Sakura Celllogienah is one example of a girl who with various limitations experienced even though not from birth can make so many learning achievements beyond those who are